O trabalho da mulher e a proteção à relação de emprego da gestante que pede demissão sem conhecimento do seu estado gravídico. - Lima, Lucas Barbalho de (2016)
The current research is dedicated to an important theme of the Labor Law, which is the Maternity Protection. It is notorious that there was a significant advancement from the first Brazilian legal standards for the protection of women's work since 1932, but the last changes are the ones that continue to cause strong legal debate, in particular the changes that occurred in 2004, when the conception of the unborn began to be regarded as the starting point for protection and, in 2012, when the guardianship was recognized for women who become pregnant in the course of the contract for a fixed term, of the contract by experience or while serving the previous notice. However, there are still situations where pregnant women are not being protected by the Labour Law, as with those who ask for dismissal without knowing of their pregnancy status, causing the waiver of rights and, therefore, in a vulnerable position for her and, especially, for the unborn child which is also considered the holder of the rights for the mothers’. At first, the law protects pregnant women only against unjustified or arbitrary dismissal, as set out in Article 10 b, II, ADCT, with no specific protection if she expressed formal interest to terminate the employment contract. However, maternity protection begins from the moment of conception the unborn child instead of when the women take notice of pregnancy; The Labor Law prohibits the waiving of labor rights and seeks to boost social worker conditions; the manifestation of the will to terminate the employment contract without knowledge of the rights acquired concerning pregnancy, it is considered a declaration of intent addiction, making voidable the legal act; the Maternity Protection holder is not only pregnant women but especially the unborn, and maternity protection is the preservation of life and maintenance of the human species. Thus, the initial hypothesis is that it is possible to recognize the pregnant protection for the women that quits without knowledge of their pregnancy status, applying all the rights and guarantees intended to pregnant women by the Labour Law. As for the methodology of this study, it is considered bibliographic and jurisprudential, qualitative, and the method is deductive. Finally, we come to the conclusion about the possibility of a systemic interpretation to recognize the mother's protection who wants to continue the employment contract where she resigned without knowing of their pregnancy status.